2018
DOI: 10.2147/jpr.s168516
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted physical pain sensation by social exclusion in women with dysmenorrhea

Abstract: PurposeDysmenorrhea (DM), which involves both acute and chronic pain, is associated with abnormalities in pain modulation. Previous studies have shown that social pain relies on some of the same neural regions that process physical pain, highlighting a possible physical–social pain overlap. However, evidence suggesting that social pain modulates the sensitivity to physical pain remains controversial. The present study aimed to assess the effects of social pain manipulation on sensitivity to physical pain in DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
(61 reference statements)
1
5
0
1
Order By: Relevance
“…Given that PPI values are negative here (Figure 3E), higher PPI values (FC) indicate that PDM females demonstrate a smaller reduction in connectivity during social exclusion, suggesting that PDM alters the response of the ACC-HIPP pathway under social pain conditions. Interestingly, our previous behavioral evaluations showed that PDM females have a higher physical pain threshold in social exclusion situations (Yu et al, 2018). Therefore, the smaller reduction in FC between the ACC and the HIPP, as reported here, seems to be associated with a higher threshold of physical pain and reduced pain perception during social exclusion in PDM females.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Given that PPI values are negative here (Figure 3E), higher PPI values (FC) indicate that PDM females demonstrate a smaller reduction in connectivity during social exclusion, suggesting that PDM alters the response of the ACC-HIPP pathway under social pain conditions. Interestingly, our previous behavioral evaluations showed that PDM females have a higher physical pain threshold in social exclusion situations (Yu et al, 2018). Therefore, the smaller reduction in FC between the ACC and the HIPP, as reported here, seems to be associated with a higher threshold of physical pain and reduced pain perception during social exclusion in PDM females.…”
Section: Discussionsupporting
confidence: 67%
“…Interestingly, our previous behavioral evaluations showed that PDM females have a higher physical pain threshold in social exclusion situations ( Yu et al, 2018 ). Therefore, the smaller reduction in FC between the ACC and the HIPP, as reported here, seems to be associated with a higher threshold of physical pain and reduced pain perception during social exclusion in PDM females.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Además de la intensidad del dolor psicológico, las características de los participantes también parecen determinar el impacto de la exclusión social sobre la percepción de dolor físico. Yu et al (2018) analizaron el papel modulador del dolor social sobre la sensación de dolor físico agudo en mujeres con dismenorrea y sanas. El umbral y la tolerancia al dolor fue comparado en 59 mujeres con dismenorrea y en 55 mujeres controles sanas expuestas a exclusión vs. inclusión social con la prueba cyberball.…”
Section: Interesados Por Estos Resultados Aparentemente Contradictorios Bernstein Yunclassified